1995
DOI: 10.1152/jappl.1995.79.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Relative expansion of extracellular water in obese vs. normal children

Abstract: This preliminary communication reports data regarding the distribution between intracellular (ICW) and extracellular (ECW) water compartments in a group of 21 prepubertal young obese children of both sexes in comparison with a group of 18 normal children weight matched for age. Our data indicate that obesity is associated with a highly significant relative expansion of extracellular water (ECW/ICW = 0.61 +/- 0.19 and 0.76 +/- 0.09 in control and obese subjects, respectively; P < 0.0015). This observation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 0 publications
3
20
0
2
Order By: Relevance
“…Subjects had fasted for at least eight hours and voided the bladder before receiving orally a precisely weighed solution made up of D 2 O, NaBr and drinkable water. We had previously shown that D 2 O and Br reach the equilibrium in the plasma of obese children between 2.5 and 3.0 h after their administration (Battistini et al, 1992;Battistini et al, 1995b). This time is comparable to that observed in control children.…”
Section: Anthropometrysupporting
confidence: 59%
See 2 more Smart Citations
“…Subjects had fasted for at least eight hours and voided the bladder before receiving orally a precisely weighed solution made up of D 2 O, NaBr and drinkable water. We had previously shown that D 2 O and Br reach the equilibrium in the plasma of obese children between 2.5 and 3.0 h after their administration (Battistini et al, 1992;Battistini et al, 1995b). This time is comparable to that observed in control children.…”
Section: Anthropometrysupporting
confidence: 59%
“…These Authors have convincingly shown that obese women have a reduced body hydration and an expanded ECW:ICW ratio in comparison to control women. More recently, we have shown that similar alterations in body water distribution occur in obese children (Battistini et al, 1995b). These ®ndings suggest that standard methods for the assessment of body composition may require adjustments for use in obese subjects.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…It would also draw attention on the effects of treatment (diuretics, etc) on metabolism. In obese patients where a extracellular expansion is demonstrated (Battistini et al, 1995;Waki et al, 1991), metabolic data would be useful to challenge the theory.…”
Section: Discussionmentioning
confidence: 99%
“…While an assumed constant is a reasonable approximation for normal adult men and women, the assumption may not be valid in other physiological states such as childhood, old age, extreme obesity, or diseased conditions. Obesity in children, e.g., is associated with a highly significant relative expansion of ECW (Battistini et al, 1995) but not TBW. Extremely obese adults tend to have an expanded ECW compartment, causing TBW measurements by isotope dilution to overestimate FFM (Waki et al, 1991;Das et al, 2003).…”
Section: Body Compositionmentioning
confidence: 99%